Reconciling the Other: Travelling Objects and Collaborative Teaching - Iezaki, Moe; Novotná, Magdalena (Revija za elementarno izobraževanje, 2022)
A collaborative art education project involving Japan and the Czech Republic focused on the enculturation processes experienced by two teachers and their students, how immersion in visual arts can contribute to cultural understanding and the reconciliation of two pedagogical approaches to art. This project also addressed this reconciliation with the unknowable ‘Other’ through the creation of artwork, ‘travelling objects’ and collaborative teaching. Outcomes include similarities between objects from the two countries and two pedagogical approaches and suggest that participants strived to reconcile the Other, thus creating a spatial and relational intermediate space by dealing with those objects and communicating together.
Keywords: cultural inclusion, cultural identity, art education, collaborative learning, Other